Importance of Assessing the Effect of Statins on the Function of High- Density Lipoproteins on Coronary Plaque - Kishida, Ken; Funahashi, Tohru; Shimomura, Iichiro (Cardiovascular & Haematological Disorders - Drug Targets, 2012)
High-density lipoproteins (HDL) are small particles comprised of phospholipids and stabilizing proteins, which carry cholesterol and triglycerides in the blood stream. The incidence of cardiovascular events is high in patients with low level of HDL-cholesterol (HDL-C). In the present study, we defined The PH index [Δcoronary plaque volume/ΔHDL-C] index as a putative clinical index of cholesterol efflux capacity of HDL from atheromatous plaque. The present study investigated the PH index in response to treatment with different types of HMG-CoA reductase inhibitors (statins), in contrast to similar changes in the PL index [Δcoronary plaque volume/Δlow-density lipoprotein-cholesterol (LDL-C)] by the same statins. Using the 2000-2011 PubMed database, the search keywords were “statins” and “intravascular ultrasound (IVUS)” and “plaque volume”. Cross references were checked. PubMed search identified 29 references, and finally 4 published studies were selected for data analysis. The PL index, representing the change in plaque volume induced by 1% reduction in LDL-C, showed no difference among the different statins. On the other hand, the PH index, representing the change in plaque volume induced by 1% increase in HDL-C, showed wide variability among the different statins; 1.4 by atorvastatin, 1.0 by pravastatin, -0.1 by simvastatin, -0.2 or -0.5 by rosuvastatin, and -1.8 by pitavastatin. In conclusion, the best coronary plaque regression index attributed to HDL-cholesterol elevation (PH index) was found in pitavastatin treatment, in comparison with the other 4 statins (atorvastatin, pravastatin, simvastatin, rosuvastatin) investigated in the articles scanned by their search.
Keywords: statins